2013
DOI: 10.7314/apjcp.2013.14.6.3809
|View full text |Cite
|
Sign up to set email alerts
|

Association of XRCC1 Gene Polymorphisms with Breast Cancer Susceptibility in Saudi Patients

Abstract: Background: X-ray repair cross-complementing group 1 (XRCC1) plays a key role in the base excision repair pathway, as a scaffold protein that brings together proteins of the DNA repair complex. XRCC1 is reported to be a candidate influence on cancer risk. The aim of our present study was to assess the association of rs1799782 (Arg194Trp) and rs25487 (Arg399Gln) XRCC1 gene polymorphisms with breast cancer in the Saudi population. Materials and Methods: The two SNP's were analyzed in breast cancer patients and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
(23 reference statements)
1
7
1
Order By: Relevance
“…For example, Roberts et al in Caucasians observed an increased risk of XRCC1 gene rs25487 for breast cancer in postmenopausal women [22], which was consistent with the results of the present study, as well as a recent meta-analysis by Wu et al on 44 independent case-control studies [23]. However, Al Mutairi et al in Saudi patients failed to confirm this association, and instead they found that another polymorphism rs1799782 in XRCC1 gene was associated with the significant risk of breast cancer [24]. Besides the environmental and cultural divergences, it cannot be totally ruled out that the evolutionary history of linkage disequilibrium patterns will vary significantly across different ethnic populations.…”
Section: Discussionsupporting
confidence: 92%
“…For example, Roberts et al in Caucasians observed an increased risk of XRCC1 gene rs25487 for breast cancer in postmenopausal women [22], which was consistent with the results of the present study, as well as a recent meta-analysis by Wu et al on 44 independent case-control studies [23]. However, Al Mutairi et al in Saudi patients failed to confirm this association, and instead they found that another polymorphism rs1799782 in XRCC1 gene was associated with the significant risk of breast cancer [24]. Besides the environmental and cultural divergences, it cannot be totally ruled out that the evolutionary history of linkage disequilibrium patterns will vary significantly across different ethnic populations.…”
Section: Discussionsupporting
confidence: 92%
“…The median age at diagnosis of our study was 49 years compared with very similar mean age in Saudi Arabia (48-49 years) (Al Mutairi et al, 2013), . While the median age at diagnosis for women (52.5 years) (Lakkis et al, 2010), Iran (46 years) (Taheri et al, 2012), Australia (60 years) (Australian Institute of Health, 2012).…”
Section: Iraq and United Kingdom In 2009mentioning
confidence: 49%
“…In other GWAS studies among Asians, new breast cancer risk variants at 6q14, 10q25, and 2q34 were discovered Shi et al, 2013). SNPs in several genes (i.e., XRCC1, EGFR, ATM, TP53) may be associated with breast cancer risk among Asian women, but sample sizes have been limited (Park et al, 2003;Hirose et al, 2004;Lee et al, 2005;Yuan et al, 2005;Hong et al, 2009;Faghani et al, 2011;Bag et al, 2012;Han et al, 2012;Al Mutairi et al, 2013). Although results from small case-control studies suggest gene-environment interactions for breast cancer risk among Asian women, no significant interactions were observed with a cumulative genetic risk score of 20 susceptibility loci for breast cancer and known risk factors (reproductive factors, BMI, waist-to-hip ratio, etc.)…”
Section: Discussionmentioning
confidence: 99%